"Is Water a Human Right?": Priming Water as a Human Right Increases Support for Government Action - Starzyk, Katherine B.; Neufeld, Katelin H. S.; Gaucher, Danielle; Vorauer, Jacquie D.; Fontaine, Aleah S. M.; Quesnel, Matthew S.; Yakubovich, Alexa R. (The International Indigenous Policy Journal, 2021)
Many First Nations homes in Canada do not have adequate water services.  This issue is unlikely to be resolved without public pressure on the government.  Thus, we investigated one strategy to increase non-Indigenous Canadians’ support for government action: framing water as a human right.  Informed by a partnership with Indigenous community members and multidisciplinary collaborators, we conducted seven experiments that sampled non-Indigenous Canadian community members (N = 584) and university undergraduates (N = 274).  Overall, framing water as a human right increased public support, relative to control conditions.  Further, the human rights frame indirectly increased support for government action through increases in perceived suffering (physical and financial) and empathy.  We discuss policy implications and end with a call for action.